A place to call home - 365191 Matthews, Carole author (London : Sphere, 2014)
In the dead of night, Ayesha takes her daughter, Sabina, and slips quietly from her home, leaving behind a life full of pain. Boarding a coach to London, all Ayesha wants is a fresh start. Hayden, a former popstar, has kept himself hidden away for years. He's only opened up his home to two people - Crystal, a professional dancer with a heart of gold, and Joy, an ill-tempered retiree with a soft spot for waifs and strays. When Crystal asks Hayden if Ayesha and Sabina can stay with them, he reluctantly agrees and, as different as they may be, they quickly form an unlikely bond. So when enemies threaten their peaceful home, they will do all they can to save it and each other. Uplifting and emotional, this is a novel of new beginnings, of discovering love and of finding A Place to Call Home.